Parameters and Biomechanics of Cervical Sagittal Balance: A Concise and Precise Review - Shrestha, Prabin; Shidoh, Satoka; Lee, Jangbo; Yamaguchi, Satoshi (Nepal Journal of Neuroscience, 2024)
Cervical spine is a vital component of the human spine and it is different from other components. It is the most mobile part of spine and it not only holds the head load but also maintains head balance while in motion. It also helps to balance the thoracic spine which is just contrary to it. Thoracic spine is a rigid structure and its natural curve is kyphotic unlike cervical spine. The equilibrium maintained by the cervical spine for head holding and balancing thoracic kyphosis is called cervical sagittal balance.  Similarly, cervical spine also maintains the balance with lumbar spine and its lordosis. In fact, various components of the human spine are not individual parts from a function standpoint, they act simultaneously in a coordinated way to maintain the global balance so that human body remains in an equilibrium at any posture and position, this is what is called a sagittal balance. Cervical spine plays a vital role in maintaining the global balance of spine.  Many parameters have been identified to understand cervical sagittal balance. Surgical planning based on maintenance of sagittal balance with the help of these parameters gives the best outcome.  We hereby have tried to collect the maximum information about cervical sagittal balance which otherwise is not mentioned collectively elsewhere, and this will provide guidelines and surgical hints to a spinal surgeon.